Smad4/DPC4-mediated tumor suppression through suppression of angiogenesis - Schwarte-Waldhoff, Irmgard (The National Academy of Sciences, 2000)
Smad4/DPC4 (deleted in pancreatic carcinoma, locus 4) is a tumor suppressor gene lost at high frequency in cancers of the pancreas and other gastrointestinal organs. Smad4 encodes a key intracellular messenger in the transforming growth factor β (TGF-β) signaling cascade. TGF-β is a potent inhibitor of the growth of epithelial cells; thus, it has been assumed that loss of Smad4 during tumor progression relieves this inhibition. Herein, we show that restoration of Smad4 to human pancreatic carcinoma cells suppressed tumor formation in vivo, yet it did not restore sensitivity to TGF-β. Rather, Smad4 restoration influenced angiogenesis, decreasing expression of vascular endothelial growth factor and increasing expression of thrombospondin-1. In contrast to the parental cell line and to control transfectants that produced rapidly growing tumors in vivo, Smad4 revertants induced small nonprogressive tumors with reduced vascular density. These data define the control of an angiogenic switch as an alternative, previously unknown mechanism of tumor suppression for Smad4 and identify the angiogenic mediators vascular endothelial growth factor and thrombospondin-1 as key target genes.